Planning and Performance in Small Groups: Collective Implementation Intentions Enhance Group Goal Striving - Thürmer, J. Lukas; Wieber, Frank; Gollwitzer, Peter M. (Frontiers in Psychology, 2017)
There are two key motivators to perform well in a group: making a contribution that (a) is crucial for the group (indispensability) and that (b) the other group members recognize (identifiability). We argue that indispensability promotes setting collective (“We”) goals whereas identifiability induces individual (“I”) goals. Although both goals may enhance performance, they should align with different strategies. Whereas pursuing collective goals should involve more cooperation, pursuing individual goals should involve less cooperation. Two experiments support this reasoning and show that planning out collective goals with collective implementation intentions (cIIs or “We-plans”) relies on cooperation but planning out individual goals with individual implementation intentions (IIs or “I-plans”) does not. In Experiment 1, three-member groups first formed a collective or an individual goal and then performed a first round of a physical persistence task. Groups then either formed a respective implementation intention (cII or II) or a control plan and then performed a second round of the task. Although groups with cIIs and IIs performed better on a physical persistence task than respective control groups, only cII groups interacted more cooperatively during task performance. To confirm the causal role of these interaction processes, Experiment 2 used the same persistence task and manipulated whether groups could communicate: When communication was hindered, groups with cIIs but not groups with IIs performed worse. Communication thus qualifies as a process making cIIs effective. The present research offers a psychology of action account to small group performance.